2019
DOI: 10.1186/s12904-019-0421-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards appropriate information provision for and decision-making with patients with limited health literacy in hospital-based palliative care in Western countries: a scoping review into available communication strategies and tools for healthcare providers

Abstract: Background Person-centred palliative care poses high demands on professionals and patients regarding appropriate and effective communication and informed decision-making. This is even more so for patients with limited health literacy, as they lack the necessary skills to find, understand and apply information about their health and healthcare. Recognizing patients with limited health literacy and adapting the communication, information provision and decision-making process to their skills and need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 36 publications
1
40
0
3
Order By: Relevance
“…A recent review conducted by Noordman and colleagues identified current strategies and tools in use by healthcare providers for communication in palliative care [30]. Face-to-face communication strategies include: the teach-back method where patients repeat back information communicated to them, jargon-free communication, and adopting a slow rate of speech [30]. Written and online strategies include supplemental graphs and illustrations for conversation, and using short sentences and paragraphs [30].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent review conducted by Noordman and colleagues identified current strategies and tools in use by healthcare providers for communication in palliative care [30]. Face-to-face communication strategies include: the teach-back method where patients repeat back information communicated to them, jargon-free communication, and adopting a slow rate of speech [30]. Written and online strategies include supplemental graphs and illustrations for conversation, and using short sentences and paragraphs [30].…”
Section: Discussionmentioning
confidence: 99%
“…Face-to-face communication strategies include: the teach-back method where patients repeat back information communicated to them, jargon-free communication, and adopting a slow rate of speech [30]. Written and online strategies include supplemental graphs and illustrations for conversation, and using short sentences and paragraphs [30]. Tools (patient decision aids and question prompt lists) were also identified in one study to facilitate patient-provider communication [30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations